Patient‐Reported Outcome Information Collected from Lupus Patients Using a Mobile Application: Compliance and Validation. Issue 2 (10th November 2021) - Bell, Kristy; Dykas, Claire; Muckian, Bridget; Williams, Brooke; Rainey, Hope; Comberg, Maggy; Mora, Mary; Owen, Katherine A.; Lipsky, Peter E.
Abstract : Objective: Patient‐reported outcomes (PROs) can provide critical information concerning the impact of a disease on an individual. Mobile technology to collect PRO data in an electronic format (ePRO) allows for frequent assessment in the person's regular environment. The goal of this study was to assess the compliance with a phone application (app) and validate ePRO information in individuals with systemic lupus erythematosus (SLE). Methods: A smartphone app that collects ePRO data from various clinical instruments was developed. Information was collected by both an ePRO and a paper‐administered instrument as part of a multicenter randomized interventional clinical trial of patients meeting American College of Rheumatology (ACR) criteria for the classification of SLE. To determine agreement between PRO information collected in the different formats, intraclass correlation coefficients (ICCs), paired Student's t tests, and Bland–Altman plots were evaluated. Compliance and Cronbach's alpha were also assessed as a measure of survey reliability. Results: For the 62 subjects from diverse ancestral backgrounds, compliance with ePRO completion was high (more than 75%). Cronbach alpha values for PROs indicated moderate to high survey reliability. The vast majority (73.4%) of ICC values were indicative of good to excellent reliability between measurement methods. Bland–Altman plots verified method agreement, and 87% of pairwise t tests yielded an insignificant difference between information collected with the different administration methods. Conclusion: The excellent compliance and the high level of consistency between data collected by paper and that collected by electronic methods indicate that the app provides a reliable means of cataloging real‐time changes in PROs in SLE patients.